UV‐Sinterable Silver Oxalate‐Based Molecular Inks and Their Application for In‐Mold Electronics. (18th July 2021) - Liu, Xiangyang; Li, Derek; Fukutani, Hiroshi; Trudeau, Paul; Khoun, LoleÏ; Mozenson, Olga; Sampson, Kathleen L.; Gallerneault, Mary; Paquet, Chantal; Lacelle, Thomas; Deore, Bhavana; Ferrand, Olivier; et al.
Abstract: A new broadband UV light‐based processing method for a screen printable silver oxalate molecular ink is developed that enables structural electronics to be produced on complex thermoformed 3D objects. The production of these 3D devices is driven by the light‐induced reduction of silver oxalate to form an interfacial silver nanoparticle layer that allows the ink to transition to a viscous liquid intermediate and elongate up to 50% without cracking during thermoforming. Ultimately, this enables the development of 3D electronics devices with significantly less limitations on geometry, shape, size, and depth in comparison to commercially available inks. UV processing is also effective for 2D traces on low temperature PET substrate, where in situ produced silver nanoparticles can subsequently absorb light and further facilitate the rapid conversion of the silver oxalate to metallic silver through a self‐limiting thermal decomposition. The resulting traces have superior electrical properties and are produced in significantly less time in comparison to thermal sintering. Together, UV processing and the silver oxalate molecular ink serve as a platform for both the rapid production of conductive silver traces on low temperature substrates and the development of novel thermoformed 3D human‐machine interface devices, areas of interest for both academia and industry. Abstract : A new broadband UV light‐based processing method for a silver oxalate‐based molecular ink allows for the production of conductive traces with thermoforming‐induced elongations up to 50%. These remarkable trace elongations can further enable the development of new 3D human‐machine interface devices with geometries, shapes, and depths that are otherwise unattainable.